The wrong side of the law - Compton, Ralph; Randisi, Robert J. (Gunfighter series., 2021)
Tired of being on the wrong side of the law, bandit Tom Palmer takes the identity of a dead lawman and heads to the town of Integrity, South Dakota where he takes over as the local sheriff, hiding in plain sight.